Perception of Teachers, Students & Parent About The Impact of Mid-day Meal Scheme on Improving Health Status of The Students In Punjab - RANI, KANCHAN (Gyan Management Journal, 2019)
Mid Day Meal Scheme is a well-intentioned programme to address all fundamental problems of health, education and overall development of children in the country. MDM could serve as an important purpose in nurturing the buds and focusing on learning and filling the empty stomach contributing towards equality. Present study on MDM scheme was carried out to assess the impact of the scheme on health status of the students in three districts namely Sangrur, Barnala and Mansa of Punjab. Based on the analysis, suggestions have been recommended for ensuring proper implementation of mid-day meal scheme. The findings of the study will be of apparent interest to the administrators and educational policy makers. It also underscores the need for better and more extensive evaluations that can inform us of the specific appeal of this scheme.